Australian Coastal Flooding Trends and Forcing Factors. Issue 2 (11th February 2022) - Hague, Ben S.; Jones, David A.; Jakob, Doerte; McGregor, Shayne; Reef, Ruth
Abstract: Using the new Australian National Collection of Homogenized Observations of Relative Sea Level (ANCHORS) dataset, we assess trends in Australian relative sea levels over recent decades and subsequent coastal flooding impacts. We estimate a gauge average rate of mean sea level rise over the 1966–2019 period of 1.94 mm/yr with local variations around the Australian continent. Simultaneously, the frequency of coastal flooding impacts has increased at many major Australian cities including Sydney, Melbourne, Brisbane, Adelaide, and Perth. We find that this increase is not because storm surges are getting larger or more frequent, but because tides are reaching higher levels as they rise and fall about higher mean sea levels. This demonstrates that a major shift in the processes that lead to coastal flooding is underway, arising directly from global mean sea level rise, and is consistent with findings from the United States. This suggests that new perspectives on extreme sea levels are required, so research can be more impact‐based and meet the needs of policymakers planning for these impacts. Considering extreme sea levels more broadly, we show that the seasonality of extreme sea levels is closely linked to the monthly variability in the heights of the highest tides. This framework provides a holistic assessment of coastal flood risk in Australia, based on established impact‐based methodologies. Plain Language Summary: Here, we estimate how sea level rise around Australia and its implications for the frequency of coastal flood events. We estimate that sea levels have risen more than 10 cm over the 1966–2019 period, with much of this increase happening since 1993. This has led to more frequent coastal flooding in many major cities as the daily tides reach higher levels because they now rise and fall about higher mean sea levels. This means that smaller storm surges (temporary increases in water level due to severe weather), and in some locations, tides alone, can cause coastal flooding. We show that the most frequently occurring coastal flood impacts are due to tides rather than storm surges. While these events are associated with less severe impacts than those associated with much rarer, large storm surges (e.g., from tropical cyclones), they can still lead to disruption and economic costs, especially if they occur very frequently. Hence, understanding the trends and drivers of these minor floods is important for a holistic assessment of coastal flood risk in Australia. By leveraging established impact‐based approaches we offer a new way to study the changing risk of coastal flooding in Australia. Key Points: Sea levels have risen around Australia by more than 10 cm over the last 50 yr, with most of this rise occurring since 1993 Nuisance and minor floods are becoming more frequent at Australia's major population centers, largely driven by increases in tidal flooding These coastal floods, and extreme sea levels more generally, exhibit seasonality linked to the monthly variability in heights of high tides